Treatment with Y-27632, a ROCK Inhibitor, Increases the Proinvasive Nature of SW620 Cells on 3D Collagen Type 1 Matrix - Ramana Vishnubhotla; Shruthi Bharadwaj; Shan Sun; Vitali Metlushko; Sarah C. Glover (International Journal of Cell Biology)
The concept of using tissue density as a mechanism to diagnose a tumor has been around for centuries. However, this concept has not been sufficiently explored in a laboratory setting. Therefore, in this paper, we observed the effects of cell density and extracellular matrix (ECM) density on colon cancer invasion and proliferation using SW620 cells. We also attempted to inhibit ROCK-I to determine its effect on cell invasion and proliferation using standard molecular biology techniques and advanced imaging. Increasing cell seeding density resulted in a 2-fold increase in cell invasion as well as cell proliferation independent of treatment with Y-27632. Increasing collagen I scaffold density resulted in a 2.5-fold increase in cell proliferation while treatment with Y-27632 attenuated this effect although 1.5 fold increase in cell invasion was observed in ROCK inhibited samples. Intriguingly, ROCK inhibition also resulted in a 3.5-fold increase in cell invasion within 3D collagen scaffolds for cells seeded at lower densities. We show in this paper that ROCK-I inhibition leads to increased invasion within 3D collagen I microenvironments. This data suggests that although ROCK inhibitors have been used clinically to treat several medical conditions, its effect largely depends on the surrounding microenvironment.